Accumulation of Betaine in the Developing Mouse Oocyte Requires Choline Dehydrogenase - McClatchie, Taylor (Université d'Ottawa / University of Ottawa, 2018)
In the developing mouse oocyte, as well as in the preimplantation embryo, betaine (N,N,N-trimethylglycine) plays an important role first as a mechanism for cell volume regulation and second as a major methyl donor. Thus, the presence of betaine has implications both during development, and throughout the lifespan. It has previously been observed that betaine accumulates in the mouse oocyte as it matures, however its origin in the egg is unknown. Here I explore the enzyme choline dehydrogenase (CHDH; EC 1.199.1) as a method by which the mouse oocyte synthesizes the betaine that we observe prior to initiation transport activity in the preimplantation embryo. I carefully monitored betaine transport throughout meiotic maturation to confirm that no other previously unobserved membrane transport existed in the maturing oocyte. However, no betaine transport into oocytes was detected during meiotic maturation suggesting de novo synthesis. Previous data suggests that the enzyme is expressed (at the transcript level) in the developing oocyte, and becomes active during meiotic maturation. I demonstrated the presence of CHDH protein in the oocyte and preimplantation embryo. I then examined whether the mouse oocyte synthesizes betaine autonomously and addressed whether CHDH is a requirement for this process. Chdh knockout oocytes did not accumulate betaine in vivo, while normal betaine levels were observed in Chdh wildtype oocytes. CHDH-mediated synthesis of betaine was directly confirmed by detection of increased betaine in oocytes matured in vitro in the presence of choline. Chdh-/- oocytes failed to produce betaine when similarly cultured in choline. This establishes the production of betaine as an autonomous process in maturing oocytes. Overall, I have built upon previous data to demonstrate that betaine accumulation is a feature of meiotic maturation that occurs by de novo synthesis of the molecule, a process that requires transient activation of the enzyme choline dehydrogenase.
Keywords: choline; enzyme; gene knockout; meiosis; mouse; oocyte; betaine; choline dehydrogenase